31‐1: Invited Paper: Eyeglasses‐Style Maxwellian‐View Near‐eye Display with Lens‐Array‐Based Holographic Optical Element. Issue 1 (28th June 2021) - Xia, Xinxing; Guan, Yunqing; Yang, Furong; Mei, Yu; Zheng, Huadong; Yu, Yingjie
Abstract : We propose a novel design to implement eyeglasses‐style Maxwellian‐view near‐eye display for augmented reality. In our design, holographic optical element is fabricated and used as an off‐axis lens array to expand the eyebox for near‐eye display. A prototype with eyeglasses‐style compact form factor was successfully developed using a micro projector module as the display source and the prototype is successfully to achieve 60° wide field‐of‐view (FOV) and 10mm×10mm eyebox.